2015
DOI: 10.1038/mi.2014.40
|View full text |Cite
|
Sign up to set email alerts
|

Lymph-borne CD8α+ dendritic cells are uniquely able to cross-prime CD8+ T cells with antigen acquired from intestinal epithelial cells

Abstract: Cross-presentation of cellular antigens is crucial for priming CD8+ T cells, and generating immunity to intracellular pathogens—particularly viruses. It is unclear which intestinal phagocytes perform this function in vivo. To address this, we examined dendritic cells (DCs) from the intestinal lymph of IFABP-tOVA 232-4 mice, which express ovalbumin in small intestinal epithelial cells (IECs). Among lymph DCs (LDCs) only CD103+ CD11b− CD8α+ DCs cross-present IEC-derived ovalbumin to CD8+ OT-I T cells. Similarly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 30 publications
9
97
0
1
Order By: Relevance
“…In agreement with a critical role for CCR7 in this process (9,13,39), we show that the accumulation of BrdU-labeled CD103 + DCs in the MLN is essentially shut off in CCR7 2/2 mice. Further to this, our BrdU pulse-chase experiments show that MHC-II high DCs accumulate with a delayed kinetics in the MLN as compared with their MHC-II low counterparts, which is consistent with the MHC-II high phenotype of all DCs in mesenteric lymph (15,40). This result therefore confirms that relative expression levels of MHC-II can be used as a criterion for discriminating between migratory and resident DCs in the MLN.…”
Section: Discussionsupporting
confidence: 74%
“…In agreement with a critical role for CCR7 in this process (9,13,39), we show that the accumulation of BrdU-labeled CD103 + DCs in the MLN is essentially shut off in CCR7 2/2 mice. Further to this, our BrdU pulse-chase experiments show that MHC-II high DCs accumulate with a delayed kinetics in the MLN as compared with their MHC-II low counterparts, which is consistent with the MHC-II high phenotype of all DCs in mesenteric lymph (15,40). This result therefore confirms that relative expression levels of MHC-II can be used as a criterion for discriminating between migratory and resident DCs in the MLN.…”
Section: Discussionsupporting
confidence: 74%
“…CD103 SP DCs are capable of migrating to the MLN, share a developmental pathway with CD8α + splenic DC, and are proficient in cross-presentation (Cerovic et al, 2013; Cerovic et al, 2015; Edelson et al, 2010; Ginhoux et al, 2009). Whether they play a non-redundant role in commensal CD4 Th17 cell responses is not known.…”
Section: Resultsmentioning
confidence: 99%
“…CD103 + DCs express CCR7 and migrate to MLN to deliver antigens for T cell priming (Bogunovic et al, 2009; Cerovic et al, 2015; Johansson-Lindbom et al, 2005; Koscso et al, 2015; Schulz et al, 2009). Previous studies have shown that purified DP DCs are efficient in skewing non-commensal transgenic CD4 T cells toward Th17 cell differentiation in vitro (Denning et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the small intestine, CD103 + CD11b − (which are all CD8 + ), as well as CD103 − CD11b + and CD103 − CD11b − F4/80 -DCs are present, with CD103 -cells making up 15% of DCs, and all expressed similar amounts of CCR7 and Flt3 mRNA and expanded in the presence of exogenous Flt3L (Cerovic et al, 2014;Persson et al, 2013). Only CD103 − CD11b − cells were absent in the small intestine of RORγt-deficient mice that also lack organized lymphoid tissues, indicating that three populations of potentially migratory DCs are present in the LP, while one is present within lyphoid follicles (Cerovic et al, 2013).…”
Section: Migration From the Lamina Propria To Mesenteric Lnsmentioning
confidence: 98%